Life, Ideals and Learning(s) to be a ‘Teacher’ in B.Ed. An Analysis of the Literature of B.Ed. Programme - Sharma, Ram Murti; George, Alex M. (JOURNAL OF INDIAN EDUCATION, 2017)
The central concern of this paper is to present an analysis of the definitions and images of an ideal teacher while being trained in B.Ed. programmes in India. The study explores this theme with the help of student-teacher interactions, interactions with faculty members as well as textbooks and other study material through which the author traverses. These interactions between student-teachers and teacher-educators look into their experiences in the classroom, hostel life, teaching practice and assignments. These aspects have been contextualised and woven along with broader experiences and exposure that the author gained while working in the field of education prior to the programme and the disjuncture that has come to permeate the ideals in teacher education programme. The paper uses these narratives to critique the teacher education programme as well as to highlight its stagnation. The data for this study emerged through detailed documentation, while the author was a student as well as through further discussions after the completion of the programme. The paper also looks at a series of studies that emerge from teacher biographies, teacher-educators’ research, analysis and studies on teacher education programmes, along with discussions on the definitions of an ‘ideal teacher’.